Develop an efficient and sustainable process for biodiesel production via transesterfication - Alsharifi, Mariam Fares Abdulnabi (Curtin University, 2020)
In this thesis, metal mixed oxides (Li/TiO2) and chicken bone based catalysts (Li-Cb, Li/Zn-Cb) were prepared by wet impregnation method, characterized by several spectroscopic and analytical techniques, and performed in the transesterfication of fresh and waste canola oil for biodiesel production under different reaction conditions of reaction time, reaction temperature, and methanol to oil molar ratio. The Li/Zn-Cb catalyzed transesterfication process was evaluated under the ultrasonic conditions and optimized by Box Behnken Design (BBD).